Pengaruh Camaraderie & Work Life Balance pada Kesiapan Gen Z Bekerja Onsite - Syifa, Nadinda Putri; Saragih, Eva Hotnaidah (Indonesian Business Review, 2025)
This study is a continuation of the exploratory research conducted by Rasendriyo & Saragih (2023), with the aim of testing the significance of the influence of Camaraderie and Work-Life Balance on Generation Z's readiness to work onsite. The type of research conducted is basic research with a quantitative approach in the form of a survey using an electronic questionnaire distributed to 400 Generation Z employees working in the DKI Jakarta area via social media for one week. 372 data that met the criteria as samples were then processed using JASP software. This study found that Camaraderie and Work-Life Balance have a significant positive effect on Gen Z's Readiness to Work Onsite.